Impact of Convective Parameterizations on Atmospheric Mesoscale Kinetic Energy Spectra in Global High‐Resolution Simulations - Zongheng Li; Jun Peng; Lifeng Zhang (Geophysical Research Letters, 2023)
Abstract The responses of atmospheric kinetic energy (KE) spectra to three convective parameterizations (CPs) in global high‐resolution simulations are revealed. The results show that the KE spectra exhibit high sensitivity to the CPs, mainly at mesoscales in the middle and upper troposphere. The New Tiedtke scheme produces the steepest mesoscale slope, followed by the Kain‐Fritsch scheme and then the Grell‐Freitas scheme. In general, there is a compensating relationship between latent heat released by the CP and microphysics parameterization (MP). The less latent heat released by the CP is compensated by the more latent heat released by the MP. The shallowest mesoscale spectra for the Grell‐Freitas scheme are related to the strongest downscale cascade dominated by the rotational component of the flow, and this is attributed to more latent heat released from MP enhancing the intensity of vorticity in the troposphere and producing more gravity wave activities in the lower stratosphere.